Blood transfusions post kidney transplantation are associated with inferior allograft and patient survival—it is time for rigorous patient blood management - Hassan, Sevda; Mumford, Lisa; Robinson, Susan; Foukanelli, Dora; Torpey, Nick; Ploeg, Rutger J.; Mamode, Nizam; Murphy, Michael F.; Brown, Colin; Roberts, David J.; Regan, Fiona; Willicombe, Michelle (Frontiers in Nephrology, 2023)
Patient Blood Management (PBM), endorsed by the World Health Organisation is an evidence-based, multi-disciplinary approach to minimise inappropriate blood product transfusions. Kidney transplantation presents a particular challenge to PBM, as comprehensive evidence of the risk of transfusion is lacking. The aim of this study is to investigate the prevalence of post-transplant blood transfusions across multiple centres, to analyse risk factors for transfusion and to compare transplant outcomes by transfusion status.This analysis was co-ordinated via the UK Transplant Registry within NHS Blood and Transplant (NHSBT), and was performed across 4 centres. Patients who had received a kidney transplant over a 1-year period, had their transfusion status identified and linked to data held within the national registry.Of 720 patients, 221(30.7%) were transfused, with 214(29.7%) receiving a red blood cell (RBC) transfusion. The proportion of patients transfused at each centre ranged from 20% to 35%, with a median time to transfusion of 4 (IQR:0-12) days posttransplant.On multivariate analysis, age [OR: 1.